Pengaruh Stres Kerja Terhadap Kinerja Karyawan padaPerusahaan Batik Brotoseno Sragen - Nastiti, Yasinta Endah; , Lukman Hakim, S.E.,M.Si (2016)
This study aimed to analyze the environmental effects of work stress, work stress organizational and individual work stress on employee performance and determine the most dominant variable affecting the performance of employees at the company Batik Brotoseno Sragen. Sample collection techniques in this study using simple random sampling technique which amounts 75 respondents. The independent variable of this research that the stress of work environment, stress of work organization, and individual work stress, while the dependent variable is the performance of employees. Analysis of the data used include validity, reliability, classic assumption test, multiple linear analysis, the coefficient of determination (R2), the t test and F test coefficient of determination (R2) of 0.317 can be said that 31.7% of work stress variables environment ( X1), the stress of work organization (X2), and individual work stress (X3) effect on the performance of employees at the company Batik Brotoseno Sragen, while the remaining 68.3% were caused by the influence of other variables outside the model that is not covered in this study. Where the results of work stress environment variable regression obtained a value of 0.229 with 0.036 significance value that indicates variable environmental work stress has a negative significant influence on employee performance. Organization of work stress variables obtained a value of 0.231 with 0.026 significance value that indicates the organization of work stress variables have a significant positive influence on employee performance. In addition, individual work stress variables obtained a value of 0.209 with 0.039 significance value that indicates the individual work stress variables have a significant positive influence on employee performance. The result of the calculation, the value of F arithmetic conclude work stress environment variables (X1), the stress of work organization (X2), and individual work stress (X3) has influence together on the performance of employees at the company Batik Brotoseno Sragen.